Fat debtors: Time discounting, its anomalies, and body mass index - Shinsuke Ikeda; Myong-Il Kang; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2009)
In view of the finding that debtors are likely to be more obese than nondebtors, we investigate whether interpersonal differences in body mass are, as in the case of debt behavior, related to those in time discounting and time discounting anomalies. The effects of time discounting on body mass index (BMI) and the probabilities of being obese, severely obese, and underweight are detected by incorporating three properties of intertemporal preferences: (i) impatience, measured by the level of the respondents' discount rate; (ii) hyperbolic discounting, where discount rates for the discounting of immediate future payoffs are higher than those of distant future payoffs; and (iii) the sign effect, wherein future negative payoffs are discounted at a lower rate than are future positive payoffs. We also find that body mass is non-monotonically correlated with age, income, and working hours. As a policy implication, body mass can potentially be controlled by changing the intertemporal structure of medical care costs.
Keywords: I10; Z00; 330; BMI; obesity; underweight; time preference; discount rate; hyperbolic discounting; procrastination; the sign effect